Analysis of the Quality of Waste Cooking Oil Resulted from Rejuvenation Using Raja Nangka Banana Peel Adsorbent with Variations in Mass of Adsorbent and Length of Adsorption Time - Devianti, Vika Ayu; Arifiyana, Djamilah (Walisongo Journal of Chemistry, 2023)
Continuous use of cooking oil at high temperatures produces oil that is no longer suitable for help because it is not good for the body’s health. So that waste cooking oil can be reused, it needs to be processed to improve its quality by utilizing waste to increase its benefits. Raja Nangka, one of the banana types, is commonly used as raw material for making fried bananas, resulting in abundant banana peel waste. Therefore, this research aims to utilize Raja Nangka peel waste to rejuvenate waste cooking oil. Raja Nangka banana peel was cut into small pieces, dried, sifted, and then activated using KOH to increase its surface area so that its adsorption capacity increases. The results showed that the greater the adsorbent mass and the longer the adsorption time, the greater the ability to reduce the acid number and peroxide value in waste cooking oil. An adsorbent mass of 10 grams and a soaking time of 150 minutes were the best results for reducing the acid number and peroxide value.